Elevated Japanese encephalitis virus activity monitored by domestic sentinel piglets in Thailand - Narong Nitatpattana (2018)
Twenty-nine domestic piglets from pig farms located in three provinces of Thailand between 2003 and 2004 were used as sentinel animals for Japanese encephalitis virus (JEV) circulation. Piglets were used as sentinel to underline, on one hand, the role of domestic pigs as JEV amplifying host and, on another hand, to point out the interest of using sentinel animals for Japanese encephalitis surveillance. JEV activity was demonstrated through i/ antibody detection using a specific ELISA test for the identification of Immunoglobulins of class M and G, ii/ virus isolation on cell culture, after experimental mosquito inoculation for virus amplification. Almost 100% and 83% of the piglets, respectively, had specific IgG and IgM JEV antibodies and 35% yielded a virus isolate. Piglets of the growing farm industry act as virus amplifier increasing the risk of transmission for the human community. Conclusively, since piglets JEV infection appears early in life and is generally clinically unnoticed, it represents an exceptional sentinel model for human health threats, which has to be considered by health authorities. © 2011, Mary Ann Liebert, Inc.